Design and development of rotary slasher (pulverizer) blades for sweet potato harvesting machine - Kakahy, Amer Najat Najmaldeen (2013)
Mechanized harvesting operations of sweet potato until now, are done in two steps at different times, at least 1 to 5 days between the two operations, or harvested manually. The presence of foliage or insufficient soil preparation can make this kind of harvesting more difficult and cause high percentage of damage more than 50%. Furthermore, the high costs of labour, harvesting time and high fuel consumption by using the conventional method were the reasons to find a new technique to harvest the sweet potato. The study focuses on the design and development of a rotary slasher (pulverizer) blade for a sweet potato harvesting machine. The newly designed machine for cutting and fragmentation of stems and leaves (vegetative portion) for the crop to facilitate the process of harvesting and extraction of tubers was fabricated in combination with the digger-harvester, to pulverize and harvest tubers in a single pass. A model slasher was first designed and fabricated at the Workshop Technology Laboratory, Department of Biological and Agricultural Engineering, Faculty of Engineering, Universiti Putra Malaysia, Serdang, Selangor, Malaysia. It consists of a rotary shaft, main support frame, ball bearings, blades, cover plate and its components. The main frame supports the shaft and carriage rails in position. The overall dimension of the slasher was 30 cm long, 26 cm wide and 26 cm high. The shaft is driven by a sprocket roller chain transmission powered by an electric motor type A4234M having 1kW power, maximum speed of 3000 rpm, 220 to 240 Voltage, 50 Hz frequency, and 5.4A current. The parameters that have major influence on the design of the prototype sweet potato harvesting machine include three types of blade (smooth, serrated edge blade with 0° inclination angle and serrated edge blade with 45⁰ inclination angle),different cutting speeds (1830, 2066, 2385, 2440 and 2533 rpm, respectively), five blade cutting angles of 20⁰, 30⁰, 40⁰, 50⁰ and 60⁰ and two different feeding angles (450 and 90°). Mild steel with material density of 7850 kg/m3 was used to fabricate the blade which was designed using Solidworks 2009 software. Length and width of blade were 140 and 160 mm respectively while the total weight of blade was 0.535 kg.The percentage of sweet potato vine pulverized that passed through thesieve (< 28mm) and the power consumption in Watts of the designed slasher was evaluated. The laboratory results indicated that the best performance was obtained from the 0° serrated edge blade type and 30° blade cutting angle. Also, the best value of the cutting and power consumption was recorded with 45° and 90° feeding angles, respectively. In addition, the best performance for interaction effects between shape of the blade and the cutting speed was at 2440 rpm cutting speed with Y-shaped blade giving the highest percentage of 92.62% of pulverized sweet potato vine passing through the sieve (< 28mm). However, the L-shaped blade gave the lowest power consumption of 47.23 Watt at 1830 rpm. The field experimental results on the influence of different cutting speeds on percentage of sweet potato vine pulverization for different varieties of sweet potato vine having different moisture contents indicated that all the treatments were significant at p ‹ 0.01 significance level for percentage of sweet potato vine pulverized passing through the sieve (< 28mm) and the fuel consumption. On interaction effects between the moisture content of plant, sweet potato varieties and the mower cutting speeds, the Stone variety gave the highest percentage of sweet potato vine pulverized with 89.16% passing through the sieve (< 28mm) and fuel consumption of 1.49 ml/m when tested at 22.4% moisture content and a mower speed of 2300 rpm. Analysis of variance (ANOVA) and L.S.D tests were used to analyse the data using the statistical analysis systems (SAS 9.2) 2010 software. The major impact of this research is that farmers can benefit from the advantage of combining two operations into one (the rotary slasher with the sweet potato digging machine) which would greatly reduce the labour cost incurred in sweet potato production and maximize their profit.